MODEL BIMBINGAN PERKEMBANGAN UNTUK PENGEMBANGAN KONSEP-DIRI DAN KEMATANGAN KARIR SISWA MADRASAH ALIYAH DI BANDAR LAMPUNG - Ikbal, Muhamad (2010)
The fact show that student's career self-concept and career maturity of Madrasah Aliyah don't establish yet as task and development steps. Career guidance have been carried out at Madrasah Aliyah in Bandar Lampung, but the result don't establish students career self-concept and career maturity perfectly yet. Student's career self-concept; self understanding, self awareness, self-esteem, and student's career maturity; attitude, competence are in low categories. Career self-concept and career maturity is very important for student development. If student's career self-concept and career maturity are not good, they will face difficulties in development. As the result students will not feel satisfied. This study aimed to find out of the effective model of career development guidance for establishing career self-concept; self understanding, self awareness, self-esteem and career maturity; attitude and competence students of Madrasah Aliyah. The approach was used to answer the research questions were research and development, and by using experiment method with one-group pretest-postest and pretest-postes control group design. The research found that the model of developmental career guidance can establish student's career self concept; self understanding, self awareness, self esteem and career maturity; attitude and competence effectively. Base on study result recommended to counselor in order to study, understand, and implement the model of career development guidance for help students to establish their career self-concept and their career maturity. Key Word: Developmentalguidance, career self-concept, career maturity